Legal Protection for Cooperatives Whose Customers Commit Breach of Contract: Study of Decision Number 293/Pdt.G/2021/PN MDN - Safira, Titania Melinda; Adawiyah, Rodiatun (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the legal considerations taken by judges in cases of breach of contract (default) by customers against cooperatives, based on Decision Number 293/Pdt.G/2021/PN Mdn, and to identify appropriate legal measures that can be pursued by cooperatives in resolving such cases. The research employs a normative legal method with a case study approach. Data were collected through a literature review and analyzed using a descriptive-analytical method. The findings reveal that the judge's considerations are influenced by several factors, including the terms of the contractual agreement, the supporting evidence submitted by the parties, and the contextual impact of the COVID-19 pandemic. In dealing with cases of default, cooperatives may adopt persuasive measures and engage in alternative dispute resolution mechanisms. This study contributes theoretically to the field of legal studies, particularly in understanding judicial reasoning in civil cases, and provides practical insights for cooperatives in managing contractual disputes effectively.